2017
DOI: 10.1007/s11060-017-2693-4
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab and risk of intracranial hemorrhage in patients with brain metastases: a meta-analysis

Abstract: Administration of bevacizumab to patients with brain metastases (BM) is controversial due to concerns about the increased risk of intracranial hemorrhage (ICH). This meta-analysis assessed whether the risk of ICH increases in BM patients receiving treatments that contain bevacizumab versus without. PubMed, Embase, Cochrane Library and annual meeting abstracts of the American Society of Clinical Oncology up to 13 November 2016 were searched for studies that referred to ICH complications due to bevacizumab in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Finally, targeting CSPG4-positive GMB-associated vasculature could result in acute cranial hemorrhage, with potentially lethal consequences. Clinical data obtained from GBM patients receiving the anti-angiogenetic agent bevacizumab did not reveal a significant risk of bleeding [38]. However, owing to the different functional properties and potencies of CAR-T cells and monoclonal antibodies, direct comparisons and extrapolations are difficult.…”
Section: Cspg4-car-t-cell Therapy Of Different Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, targeting CSPG4-positive GMB-associated vasculature could result in acute cranial hemorrhage, with potentially lethal consequences. Clinical data obtained from GBM patients receiving the anti-angiogenetic agent bevacizumab did not reveal a significant risk of bleeding [38]. However, owing to the different functional properties and potencies of CAR-T cells and monoclonal antibodies, direct comparisons and extrapolations are difficult.…”
Section: Cspg4-car-t-cell Therapy Of Different Tumorsmentioning
confidence: 99%
“…At the protein level, nonetheless, CSPG4 expression seems to be confined to the small intestine [34]. Moreover, CSPG4 displays a broad expression across several different cancer entities, such as melanoma [35], leukemia [36], glioma [37], triple-negative breast cancer [38], head and neck cancers [39], and mesenchymal cancers [40]. In the present review, we want to shine the light on CSPG4 as a promising target antigen for CAR-T-cell therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the side effects of BEV therapy include hemorrhage/bleeding, wound healing complications, gastrointestinal perforation, arterial thromboembolism, congestive heart failure, hypertension, proteinuria/ nephrotic syndrome, infusion-related hypersensitivity reactions, and reversible posterior leukoencephalopathy syndrome [40,41]. A meta-analysis of eight studies found that BEV treatment was not associated with a significant increase in intracerebral hemorrhage in cancer patients with BM [13]. In this study, the CNS bleeding rate with BEV treatment in NSCLC patients was 1%, which suggests that the risk of intracerebral hemorrhage is low with BEV treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of 24 randomized controlled trials found that BEV treatment improved the overall survival (OS) and PFS in patients with metastatic solid tumors but was associated with a statistically higher incidence of fatal adverse events (AEs) overall and an increased risk of fatal pulmonary hemorrhage in patients with lung cancer [12]. However, a meta-analysis of cancer patients with BM found that BEV treatment was not associated with a significantly increased risk of intracerebral hemorrhage [13].…”
Section: Introductionmentioning
confidence: 99%
“…Concerns regarding a potential association with risk of intracranial hemorrhage have discouraged the use of bevacizumab 33 . Yet, there have been studies of patients with primary brain tumors reporting clinical benefit and no significant increase in intracranial hemorrhage 34 , and a meta-analysis of eight studies covering 8,713 patients demonstrated no increase in the risk of intracranial hemorrhage in patients with brain metastases 35 .…”
Section: Discussionmentioning
confidence: 99%